A Silicon/Double-Shelled Carbon Yolk-Like Nanostructure as High-Performance Anode Materials for Lithium-Ion Battery. Issue 8 (19th May 2015) - Sun, Zhuang; Tao, Siying; Song, Xuefeng; Zhang, Peng; Gao, Lian
Abstract : Novel Si@double-shelled carbon (Si@DC) yolk-like powders have been fabricated by using the reinvented Si@void@mesoporous silica nanostructures as templates for the first time. The fabrication is quite economical without special equipment and using cheap glucose as the carbon source. In this special architecture, commercial Si nanoparticles are completely sealed inside the ultrathin and intact double-shelled carbon with rationally designed void spaces between the cores and shells, which can accommodate the volume fluctuation of Si cores. When tested as an anode material in lithium-ion batteries (LIBs), the resulting Si@DC yolk-like powders exhibit outstanding cycling stability and enhanced lithium storage capacity.